Waste PC Recycling Policy Formulation by Fuzzy Optimization Techniques - Cheng, Chi-Bin; Shih, Hsu-Shih; Hsu, Ya-Ju (Anais do Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais (WCAMA); 2014: Anais do V Workshop de Computação Aplicada a Gestão do Meio Ambiente e Recursos Naturais, 2014)
As the fast growth of information technology and the short life cycle of PC, environmental concerns regarding the disposal of waste PCs are increasing. Government regulation has played an important role in the management and recycling of electronic waste. This study attempts to formulate the recycling fee and subsidy rate for an organization which is in charge of the waste PC recycling policies in Taiwan. Fuzzy mathematical programming is used to model the decision, and a solution procedure based on intuitionistic fuzzy optimization is employed to solve the problem. The result obtained by this study is compared with the current operations by the organization.